Analisis Kesuksesan Penerapan Sistem Informasi Administrasi Kependudukan Menggunakan Model Delone Dan Mclean - Alex Yuswandi Zalukhu; Joni Yanto Gulo; Nelly Astuti Hasibuan (SNASTIKOM, 2022)
The Department.of.Population and Civil Registration (DISDUKCAPIL) of Medan City is one of the agencies that work in the field of community data. The Department of Population and Civil Registration has developed inthe field of technology, namely the application of the Population Administration Information System (SIAK). ThePopulation Administration Information System (SIAK) is one of the application software that plays an importantrole in population data collection, especially in one of the cities in North Sumatra, namely Medan City. Thisapplication is equipped with procedures and is accompanied by special standards according to the rules of thegovernment of the Republic of Indonesia. This research is entitled "Analysis of the Success of the Application ofPopulation Administration Information Systems". The.purpose.of.this study was to determine the level ofsuccess of the application of the Population Administration Information System in Medan City and to find outwhich variables were very influential in the success of SIAK. In this study, the method used by the researcher is the DeLone and McClean model using the variables of System Quality, Information Quality, UserSatisfaction and Net Benefits. From the results of thestudy, it can be seen that the application of the PopulationAdministration Information System (SIAK) carried out by the Department of Population and Civil Registrationof Medan City is in accordance with applicable rules and policies, butin practice there are still someproblems.[1]